Improving perfomance in single-link flexible manipulator using hybrid learning control - Md. Zain, Mohd. Zarhamdy; Tokhi, M. O.; Mailah, Musa; Mohamed, Zaharuddin (Faculty of Mechanical Engineering, 2004)
An iterative learning control method for a single-link flexible manipulator is proposed to achieve precise tracking control and end-point vibration suppression of the system. The learning is done in a feedback configuration with hybrid control and the learning law updates the feedforward input from the error of the previous trial. The dynamic model of the flexible manipulator is derived using the finite element method. Initially, a collocated proportional-derivative (pd) controller utilizing hub-angle and hub-velocity feedback is developed for control of rigid-body motion of the system. The controller is then extended to incorporate a non-collocated proportional-integral-derivative (pid) controller and a feedforward controller based on input shaping techniques for control of vibration flexible motion) of the system. Simulation results of the response of the manipulator with the controllers are presented in the time and frequency domains. The pe$ormance of the hybrid iterative learning control scheme is assessed in terms of input tracking and level of vibration reduction in comparison to a conventionally designed collocated pd and non-collocated pid control schemes.